“Certaine Amorous Sonnets, Betweene Venus and Adonis”: fictive acts of writing in The Passionate Pilgrime of 1612 - Lindsay Ann Reid (Etudes Epistémè)
In c. 1599, the London stationer William Jaggard produced two editions of The Passionate Pilgrime, a collection of twenty poems best known for its inclusion of five sonnets by William Shakespeare. Having been lengthened to include a total of twenty-nine poems, a third edition of this printed miscellany was released by Jaggard just over a decade later in 1612. This article centers around Jaggard’s decision to repackage the expanded contents of the 1612 Passionate Pilgrime with a title page that not only intriguingly advertises the collection’s inclusion of ‘Certaine Amorous Sonnets, betweene Venus and Adonis,’ but also draws particular attention to a newly appended pair of ‘Loue-Epistles’ purportedly written by the mythological figures Paris and Helen. Taking as my particular focus the acts of writing described on The Passionate Pilgrime’s 1612 title page, I contend that these putative acts provide audiences with a fictitious etiology of the miscellany’s origins. Like so many other early printed miscellanies, Jaggard’s volume exploits the perceived exclusivity of scribal coterie poetry; rather than positing The Passionate Pilgrime’s contents as texts commemorating actual courtly occasions between historical Tudor or Stuart elites (as earlier printed anthologies such as Richard Tottel’s Songes and Sonettes often had), however, Jaggard’s title page draws upon established generic conventions as well as the literary precedent provided by Ovid’s Heroides to reimagine acts of literary composition transpiring within a well-known mythological story-world.